Dinamika Adab Dalam Pembentukan Peradaban Islam Klasik: Studi Historis Era Abbasiyah - Ahmad Fauzi Ramdhani; Imam Mustakim; M. Rizal Fadillah (Jurnal Adab dan Peradaban Islam, 2026)
This study examines the dynamics of adab (Islamic etiquette and ethics) in the formation of classical Islamic civilization during the Abbasid era (750–1258 CE). The research aims to analyze how adab functioned as a foundational pillar in the intellectual, cultural, and political development of the Abbasid caliphate. Using a qualitative historical approach with library research design and content analysis, this study draws upon primary and secondary sources including classical Islamic manuscripts, historiographical texts, and contemporary Indonesian scholarship. The findings reveal that adab served not merely as a code of individual conduct, but as a comprehensive civilizational framework integrating scholarly ethics, governance protocols, literary aesthetics, and interfaith social norms. The translation movement (Bayt al-Hikmah) and court patronage of scholars elevated adab into a state ideology that unified diverse ethnic and religious communities under a shared intellectual identity. This study concludes that adab constitutes a civilizational heritage with profound relevance for contemporary Islamic education and the renewal of Muslim intellectual culture.